Modeling the Propensity for Extramarital Relationships Based on Narcissism and Communication Skills with the Mediating Role of Marital Burnout - Shahrabadi, Maryam; Khakpour, Reza; Rezakhani, Simindokht (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to propose a predictive model of the propensity for marital infidelity based on the roles of narcissism and communication skills as predictor variables, and marital burnout as a mediating variable. The significance of this research lies in identifying psychological factors influencing marital infidelity, which is one of the major threats to family stability and the mental health of couples. The research method was descriptive-correlational, utilizing structural equation modeling. The statistical population included married women residing in Shahriar County who had a minimum of five years of shared marital life. Among them, 240 participants were selected through multi-stage cluster sampling. Data were collected using validated psychological questionnaires and analyzed accordingly. The results revealed that narcissism and deficiencies in life skills significantly increased the propensity for marital infidelity. Moreover, marital burnout played a significant mediating role in the relationship between the predictor variables and the tendency toward infidelity. Specifically, narcissism and inadequate communication skills were shown to elevate the risk of infidelity through an increase in marital burnout. These findings can contribute to the development of preventive and therapeutic interventions in the field of family health.